2008
DOI: 10.1186/1477-7819-6-18
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus latent membrane protein-1 (LMP-1) 30-bp deletion and Xho I-loss is associated with type III nasopharyngeal carcinoma in Malaysia

Abstract: Background: Nasopharyngeal carcinoma (NPC) is a human epithelial tumour with high prevalence amongst Chinese in Southern China and South East Asia and is associated with the Epstein-Barr virus (EBV). The viral genome harbours an oncogene, namely, the latent membrane protein 1 (LMP1) gene and known variants such as the 30-bp deletion and loss of XhoI restriction site have been found. Less is known about the relationship between these variants and the population characteristics and histological type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 33 publications
1
53
0
Order By: Relevance
“…193 Based on genotyping polymorphic markers in EBER1 and 2, LMP1, BHRF1, BZLF1, and EBNA gene loci, different EBV strains have been characterized in tumor tissue from various geographic regions. [194][195][196][197][198][199] Moreover, EBV harbors different genetic variations in different ethnic and geographic poulations. [200][201][202][203][204][205][206][207][208] There is an association between the LMP1 deletion variant Asp 335 and NPC patients (tumor tissue) in Hong Kong.…”
Section: Npc and Ebvmentioning
confidence: 99%
“…193 Based on genotyping polymorphic markers in EBER1 and 2, LMP1, BHRF1, BZLF1, and EBNA gene loci, different EBV strains have been characterized in tumor tissue from various geographic regions. [194][195][196][197][198][199] Moreover, EBV harbors different genetic variations in different ethnic and geographic poulations. [200][201][202][203][204][205][206][207][208] There is an association between the LMP1 deletion variant Asp 335 and NPC patients (tumor tissue) in Hong Kong.…”
Section: Npc and Ebvmentioning
confidence: 99%
“…Efforts that have targeted specific gene regions of the virus have identified substantial genetic heterogeneity in EBV and have demonstrated that as many as 80–100% of infected individuals carry multiple EBV variants (Bell et al, 2008; Bhatia et al, 1996; Edwards et al, 1999; Gutierrez et al, 2002; Gutierrez et al, 1997; Ji et al, 2008; Sitki-Green et al, 2003; Sitki-Green et al, 2002; Tierney et al, 2006; Walling et al, 2003; Walling et al, 1999). …”
Section: Issues That Should Be Considered When Planning Future Stumentioning
confidence: 99%
“…Since references given in a previous review (Jenkins and Farrell 1996), many groups have investigated the presence of the 30-bp deletion LMP1 in normal carriers (Correa et al 2004) or a variety of EBV-associated diseases (Cheung et al 1998;Hayashi et al 1998;Zhang et al 2002;Tai et al 2004;Jen et al 2005;Chang et al 2006;Zhao et al 2005;Correa et al 2007;See et al 2008;Lorenzetti et al 2012;Banko et al 2012;Giron et al 2013). A rarer 69-bp deletion in the C-terminus has also been studied (Hadhri-Guiga et al 2006); it was reported to have a reduced ability to activate the cell AP1 transcription factor (Larcher et al 2003).…”
Section: Lmp1mentioning
confidence: 94%